Pancreatic serous cystadenoma – A case report - Bhavana Grandhi; Vissa Shanthi; Nandam Mohan Rao; Vengala Chidananda Reddy; Murali Mohan Kuppili (International Journal of Medical Research and Review, 2014)
Microcystic serous cystadenoma is a benign tumor of pancreas, also termed as Clear cell or Glycogen rich adenoma. It occurs at any site in pancreas and composed of small cystic spaces lined by small cuboidal cells with clear cytoplasm, glycogen. There is an association with von Hippel Lindau syndrome in few cases. Clinical symptoms are variable. Excision is almost curative. We report a case of 70 year old male who presented to the OPD with vague complaints of local discomfort. Ultrasound showed a mass in the pancreas. Pancreatectomy was done and diagnosed as microcystic serous cystadenoma of pancreas on histopathology.